Creative (and Cultural) Industry Entrepreneurship in the 21st Century - Hill, Inge (Emerald Publishing Limited, 2023)
Both volumes of Creative (and Cultural) Industry Entrepreneurship in the 21st Centurymap and elucidate the adaptations and challenges faced by the creative professionals and the entrepreneurial solutions they have co-developed
Description based on publisher supplied metadata and other sources